Effect of Variety, Nitrogen Levels and their Interactions on Proximate and Mineral Composition of Sorghum - Yashim, S.M.; Zakka, T.; Ibrahim, A.M.; Usman, S. (Nigerian Journal of Animal Science, 2026)
This study was conducted to evaluate the effects of variety and nitrogen fertilization on the proximate and mineral composition of sorghum forage. Two sorghum varieties (Sweet Sorghum and SAMSORG-17) were cultivated under three nitrogen levels (0, 60, and 120 kg N/ha) in a split-plot design with three replications during the 2024 rainy season at the National Animal Production Research Institute (NAPRI), Shika, Zaria, Nigeria. Forage samples harvested at 8 and 12 weeks after sowing were analyzed for proximate (dry matter, crude protein, crude fiber, ether extract, ash, and nitrogen-free extract) and mineral (calcium, magnesium, potassium, and phosphorus) composition using standard procedures. The results revealed that both variety and nitrogen levels significantly (P<0.05) influenced most proximate parameters. Sweet sorghum recorded higher values of dry matter (97.26%), crude protein (7.94%), and nitrogen-free extract (61.47%), indicating superior forage quality. In contrast, SAMSORG-17 exhibited significantly higher crude fiber (30.46%), ash content (7.93%), and potassium concentration (1.85%), reflecting its grain-oriented genetic makeup. Nitrogen application significantly improved crude protein content, with the highest value (7.92%) obtained at 60 kg N/ha, while dry matter and NFE were highest at 120 kg N/ha. Crude fiber decreased progressively with increasing nitrogen, suggesting enhanced digestibility at higher nitrogen levels. However, ether extract and most mineral components, except potassium, were not significantly influenced by variety or nitrogen level. Significant interaction effects (P<0.05) between variety and nitrogen level were observed for all proximate traits and for calcium and potassium among the minerals. Sweet sorghum responded positively to nitrogen fertilization, particularly at 60 kg N/ha, showing notable improvements in crude protein and energy composition. In contrast, SAMSORG-17 showed minimal nutritional response to increasing nitrogen rates. The study concludes that Sweet Sorghum fertilized at 60 kg N/ha is best suited for forage production due to its favorable nutritional profile and efficient nitrogen response. The findings emphasize the need for variety-specific nutrient management strategies to optimize sorghum forage quality, improve livestock productivity, and enhance sustainable agricultural practices in Northern Guinea Savannah regions.